LEADERSHIP QUALITIES AND THEIR CONSEQUENCIES IN AN ORGANIZATIONAL CONTEXT: LITERATURE REVIEW - Githui , John Ngatia (Human Resource and Leadership Journal, 2022)
Purpose: It is argued that leadership qualities are very essential and important for the overall performance of organizations as those leaders who possess certain qualities influence the level of growth for organizations. This is notable in influencing decisions that concerns allocation of resources for the existing departments in organizations. The general assumption is that all leaders do possess the necessary and requisite qualities that would enhance the achievement of the desired goals and objectives of organizations. The foregoing is certainly not always the case as most individuals do have limited knowledge as regards the qualities that are important for individuals in the leadership positions. Methodology: The study provides the linkage between leadership qualities, followership styles or behaviors, and their impact to the overall performance of organizations. Findings: The study has established that various positive leadership qualities do positively affect individual and overall organizational performance and productivity. Further, the study established that there is a correlation between the leadership qualities exhibited by the leaders and followership styles and behaviors. Though leadership qualities directly affect both the performance of individuals and the overall organization, the impact is also dependent on the followership styles exhibited by the followers/employee. Followership styles and behaviors mediates the relationship between leadership qualities and organizational performance. The identified constructs from the study were found to have an impact on the performance of organization which would ultimately enhance the competitive advantage of the same. The research established that when positive leadership qualities are combined with followership styles such as the exemplary and pragmatist, they enhance the performance of organization in the achievement of the set goals and objectives. The paper has further highlighted the role of followership in creating that environment for optimal performance of organizations.